Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0021719
|View full text |Cite
|
Sign up to set email alerts
|

Overt Attention and Context Factors: The Impact of Repeated Presentations, Image Type, and Individual Motivation

Abstract: The present study investigated the dynamic of the attention focus during observation of different categories of complex scenes and simultaneous consideration of individuals' memory and motivational state. We repeatedly presented four types of complex visual scenes in a pseudo-randomized order and recorded eye movements. Subjects were divided into groups according to their motivational disposition in terms of action orientation and individual rating of scene interest.Statistical analysis of eye-tracking data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 32 publications
12
89
1
Order By: Relevance
“…Each image of the whole stimulus set occurred only once per participant. The images were centered on the screen and presented for 6 s each, following previous studies 23, 26, 29 . Between trials, participants had to fixate a central dot used for drift correction and to reset the eye position to the center of the screen.
Figure 2Structure of one of four experimental sessions with randomized order of blocks.
…”
Section: Methodsmentioning
confidence: 99%
“…Each image of the whole stimulus set occurred only once per participant. The images were centered on the screen and presented for 6 s each, following previous studies 23, 26, 29 . Between trials, participants had to fixate a central dot used for drift correction and to reset the eye position to the center of the screen.
Figure 2Structure of one of four experimental sessions with randomized order of blocks.
…”
Section: Methodsmentioning
confidence: 99%
“…The amygdala obviously responds more strongly to such indirectly mediated emotions. However, especially for studies on overt attention, not only the affective impact of images should be considered, but also the image characteristics which revealed a very strong impact on the attention focus (see, e.g., Kaspar and König, 2011a,b). In general, many studies use human faces to induce different emotion conditions.…”
Section: The Impact Of Emotion On Attentionmentioning
confidence: 99%
“…Rather, it could be fruitful to elucidate the specific interactions between current situational factors and time-invariant personality traits to reveal further interesting effects. In a recent study Kaspar and König (2011a), we investigated changes in eye movement parameters during complex scenes repeatedly presented in a long sequence of stimuli. In this context, we also considered the subjects' global interest in the stimulus set, as well as their general ability to stay within interesting activities without shifting prematurely to alternative activities labeled as the personality trait “action orientation regarding the performance of activities” (AOP; Kuhl, 1994).…”
Section: The Impact Of Personality Traits On Attentionmentioning
confidence: 99%
“…In Study 2, we implemented a more sophisticated design to (1) replicate the findings of Study 1, (2) enlarge the findings on neutral target images differing in gist, and (3) enable a comparison between the data of the present study and one of our previous studies [21]. The latter study serves as the baseline condition in which subjects observed images under the same natural conditions, but without an emotional context…”
Section: Introductionmentioning
confidence: 98%
“…A hierarchical model preferring cognitive top-down influences, if present [13], or a combination of both stimulus-driven and cognitive high-level aspects [14], [15], [16], emphasizes the need to consider top-down influences on attention processes. Such research on the impact of higher cognitive functions on attention concentrates on visual search, memory, or previous knowledge [9], [15], [17], [18], [19], [20], [21], [22], [23], [24], [25]. Remarkably, investigations on the impact of the emotional state as an integral part of cognition [26] on visual perception are rare.…”
Section: Introductionmentioning
confidence: 99%